2016
DOI: 10.18632/oncotarget.9074
|View full text |Cite
|
Sign up to set email alerts
|

PKG II reverses HGF-triggered cellular activities by phosphorylating serine 985 of c-Met in gastric cancer cells

Abstract: Previous studies showed that type II cGMP-dependent protein kinase G (PKG II) could inhibit the activation of epidermal growth factor receptor (EGFR). Both c-Met and EGFR belong to family of receptor tyrosine kinases (RTKs) and have high molecular analogy. However, the effect of PKG II on c-Met activation is unclear. This study was designed to investigate the inhibitory effect of PKG II on the activation of c-Met and consequent biological activities. The results from CCK8 assay, Transwell assay and TUNEL assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In previous research, we have verified that PKG II inhibited EGFR, HGFR, and VEGFR through similar mechanism: PKG II decreased the activation of the these RTKs by phosphorylating their serine/threonine residues (Jiang et al, 2013a;Wang et al, 2016a;Wu et al, 2016). However, whether PKG II inhibited the activation of PDGFRb and the detailed mechanism of the inhibition has not yet been elucidated until now.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In previous research, we have verified that PKG II inhibited EGFR, HGFR, and VEGFR through similar mechanism: PKG II decreased the activation of the these RTKs by phosphorylating their serine/threonine residues (Jiang et al, 2013a;Wang et al, 2016a;Wu et al, 2016). However, whether PKG II inhibited the activation of PDGFRb and the detailed mechanism of the inhibition has not yet been elucidated until now.…”
Section: Discussionmentioning
confidence: 85%
“…Emerging evidence suggests that PKG II, a classical protein kinase, can exert antineoplastic activity in different cancers, indicating its role as a potential anti-tumor factor (Swartling et al, 2009;Karami-Tehrani et al, 2012). In previous research we reported that PKG II could inhibit the phosphorylation/activation of several RTKs, including EGFR, HGFR, VEGFR, and IGF-1R, and the important downstream signal molecules in gastric cancer cells (Jiang al., 2013a, 2013bWu et al, 2016). PDGFRb also belongs to RTK family and shares similar molecular conformation with the other RTKs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the tumourigenesis and development of GC were closely related to the receptor tyrosine kinase (RTK) c-Met (24)(25)(26). The activation of c-Met triggers signal transduction through the MAPK or PI3K/Akt/mTOR signalling pathways, which initiates cell proliferation and migration, regulates the cell cycle and reduces cell apoptosis (24). Erk 1/2 and Akt are key members of the MAPK and PI3K/Akt/mTOR signal pathways, respectively.…”
Section: C646 Suppresses the Expression Of C-met Cyclin D1 P-aktmentioning
confidence: 99%
“…The phosphorylation of Ser985 in the juxtamembrane domain also regulates Met activation. Ser985 is phosphorylated either by protein kinase-C (PKC) or type II cGMPdependent protein kinase G (PKG II), and when Ser985 is phosphorylated, HGF-dependent Met tyrosine phosphorylation and subsequent biological responses are suppressed [64][65][66].…”
Section: The Hgf-met Signaling Pathwaymentioning
confidence: 99%